The First Delinquent Peers Are the Most Important: Examining Nonlinearity in the Peer Effect. (15th April 2016) - Rees, Carter; Zimmerman, Gregory M.
Abstract : Criminologists have long recognized the importance of peers in the etiology of delinquency. Yet, the bulk of empirical studies on this topic make the implicit assumption that the peer effect to be conditioned is linear. With few notable exceptions, prior criminological research has not thought deeply about possible nonlinearity in the peer effect. To address this issue, the present study examines whether the functional form of the relationship between peer and respondent smoking, getting drunk, and fighting is nonlinear, and whether this nonlinearity is moderated by lagged respondent delinquency. Logistic regression models on adolescents from The National Longitudinal Study of Adolescent Health indicate that the marginal effect of peer delinquency on respondent delinquency decreases as the count of delinquent friends increases, consistent with a satiation effect. Moreover, the models indicate that the nonlinear effect of peer delinquency on respondent delinquency is moderated by prior respondent delinquency.